If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3y + -20) = 21 Reorder the terms: 3(-20 + 3y) = 21 (-20 * 3 + 3y * 3) = 21 (-60 + 9y) = 21 Solving -60 + 9y = 21 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '60' to each side of the equation. -60 + 60 + 9y = 21 + 60 Combine like terms: -60 + 60 = 0 0 + 9y = 21 + 60 9y = 21 + 60 Combine like terms: 21 + 60 = 81 9y = 81 Divide each side by '9'. y = 9 Simplifying y = 9
| 10x+5=3(3x+2) | | 5m+2m-8=4m-5 | | 3r^2+26r+48=0 | | 8x-3-2x=3x+21 | | 1-(3x+5)=1x-(2x+8) | | -4x-14=10 | | 3x-4x+6=-2x+7 | | 3x-4x+6=2x+7 | | 6w^3+5w^2-6w=0 | | 7x-6=2x+39 | | 5a^2=26+24 | | 10x^2+5x+2= | | 4(3x+5)=2(9x-5) | | l+3*5=31 | | (1/2)r+6=3-2r | | (1/3)+(2/3)m=(2/3)m-(2/3) | | 1.2(x+2)=2-x | | 8y-16=4y+16 | | 5x+1-3x-9 | | 13x+(12x-2)5=4(3x+2)-9x | | a+a+8=74 | | 3x^2-6=-7x-1 | | 9w+69=900 | | x-3=31 | | 6p-20=82 | | 4m-5=40 | | b=3y | | 6x+15=53 | | 45x=900 | | 15x+25y=0 | | 15-3(6x+4)=6(11-5x)+3 | | 2t-7=5 |